Working Twice as Hard to Get Half as Far: Race, Work Ethic, and America's Deserving Poor. Issue 2 (28th January 2013) - DeSante, Christopher D.
<x xml:space="preserve">Abstract</x> Attitudes toward racialized and redistributive policies like welfare are often thought of as a function of both principled ideological positions and the underlying racial attitudes a person holds. 1996 look at racial resentment as one explanation, while Sniderman and his colleagues look to principled conservatism and authoritarianism as viable alternatives, claiming that racial resentment is merely proxying a legitimate race‐neutral commitment to equality of opportunity. This article engages this debate through an experimental design which tests whether "hard work" is rewarded in a color‐blind manner. The experimental design also affords scholars the opportunity to separate the effects of the two components of racial resentment: principled values and racial animus. The results show that American norms and implicit racism serve to uniquely privilege whites in a variety of ways.